Earlier versus later initiation of renal replacement therapy among critically ill patients with acute kidney injury: a systematic review and meta-analysis of randomized controlled trials - Tai-Shuan Lai; Chih-Chung Shiao; Jian-Jhong Wang; Chun-Te Huang; Pei-Chen Wu; Eric Chueh; Shih-Chieh Jeff Chueh; Kianoush Kashani; Vin-Cent Wu (Annals of Intensive Care, 2017)
Abstract Background Although the optimal timing of initiation of renal replacement therapy (RRT) in critically ill patients with acute kidney injury has been extensively studied in the past, it is still unclear. Methods In this systematic review, we searched all related randomized controlled trials (RCTs) that directly compared earlier and later RRT published prior to June 25, 2016, from PubMed, MEDLINE, and EMBASE. We extracted the study characteristics and outcomes of all-cause mortality, RRT dependence, and intensive care unit (ICU) and hospital length of stay (LOS). Results We identified 51 published relevant studies from 13,468 screened abstracts. Nine RCTs with 1627 participants were included in this meta-analysis. Earlier RRT was not associated with benefits in terms of mortality [relative risk (RR) 0.88, 95% confidence interval (CI) 0.68–1.14, p = 0.33] and RRT dependence (RR 0.81, 95% CI 0.46–1.42, p = 0.46). There were also no significant differences in the ICU and hospital LOS between patients who underwent earlier versus later RRT [standard means difference −0.08 (95% CI −0.26 to 0.09) and −0.11 (95% CI −0.37 to 0.16) day, respectively]. In subgroup analysis, earlier RRT was associated with a reduction in the in-hospital mortality among surgical patients (RR 0.78, 95% CI 0.64–0.96) and patients who underwent continuous renal replacement therapy (CRRT) (RR 0.80, 95% CI 0.67–0.96). Conclusions Compared with later RRT, earlier initiation of RRT did not show beneficial impacts on patient outcomes. However, a lower rate of death was observed among surgical patients and in those who underwent CRRT. The included literature is highly heterogeneous and, therefore, potentially subject to bias. Further high-quality RCT studies are warranted.